2009
DOI: 10.1161/circheartfailure.108.805374
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Vasodilators in Pulmonary Hypertension

Abstract: W hen primary pulmonary hypertension (PPH) was first described in the medical literature, it was characterized from a cardiac catheterization on a young woman who had an elevated pulmonary arterial pressure of unknown origin which, after the intravenous administration of acetylcholine, promptly fell. 1 The sentinel description of this phenomenon led to the acceptance of PPH as a medical entity in which inappropriate pulmonary vasoconstriction was a central feature. 2 Since then many series of patients with PPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 88 publications
0
11
2
Order By: Relevance
“…Our data, therefore, indicate that intra-myocyte abnormalities, if present, were overshadowed by the extensive impairment in the ''central'' (and/or ''peripheral'') cardiocirculatory adjustments. It should also be noted that our results do not rule out the hypothesis of impaired peripheral microvascular function (Rich 2009), independent of the ''central'' cardiovascular dysfunction. In fact, PAH patients may present with heightened sympathetic tonus (Nootens et al 1995a, b;Velez-Roa et al 2004;Wensel et al 2009) and endothelial dysfunction (Wolff et al 2007;Peled et al 2009) which could reduce muscle blood flow (Saltin 2007).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data, therefore, indicate that intra-myocyte abnormalities, if present, were overshadowed by the extensive impairment in the ''central'' (and/or ''peripheral'') cardiocirculatory adjustments. It should also be noted that our results do not rule out the hypothesis of impaired peripheral microvascular function (Rich 2009), independent of the ''central'' cardiovascular dysfunction. In fact, PAH patients may present with heightened sympathetic tonus (Nootens et al 1995a, b;Velez-Roa et al 2004;Wensel et al 2009) and endothelial dysfunction (Wolff et al 2007;Peled et al 2009) which could reduce muscle blood flow (Saltin 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…Mb] OS (Koga et al 2007). Therefore, although the sluggish increase in muscle microvascular O 2 delivery seemed to be determined mainly by the ''central'' cardiovascular effects of PAH, microvascular dysfunction per se should not be neglected in these patients (Rich 2009). In fact, 6/14 patients in the present study had a collagenovascular disease which is known to predispose patients to microvascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Although a minority (,15%) of patients with severe PAH respond significantly to acute pulmonary vasodilators and can be treated successfully with calcium channel blockers, most are not responsive to vasodilators and are currently treated with prostacyclin analogs, endothelin-1 receptor blockers, type 5 phosphodiesterase inhibitors, or various combinations of these agents (58). These treatments provide some improvement in the quality of life of patients, but there is no convincing evidence that they significantly prolong survival (59).…”
Section: Discovery Of Novel Pah Treatmentsmentioning
confidence: 99%
“…For example, effects on the systemic circulation or other organ systems rather than changes in the pulmonary vasculature could contribute substantially to therapeutic benefit. 41 Treatment could also affect right ventricular (RV) loading conditions in complex ways not adequately captured by invasive central measurements at rest. Small observational studies have used cardiac magnetic resonance imaging (MRI) to study the effects of PAH therapy on RV structure and function, and one has shown worsening RV performance is associated with poor outcomes independent of improvements in PVR.…”
Section: Discussionmentioning
confidence: 99%